Composición florística y estructura del bosque húmedo tropical en el piso altitudinal de 400 - 500 ms.n.m de la parroquia San José de Payamino, Cantón Loreto, Provincia de Orellana. - Vélez Muñoz, Milena Analía (2019)
The present investigation was carried out in the San José de Payamino parish of the Loreto canton of the province of Orellana, with the objective of determining the floristic composition and structure in the tropical humid forest on the altitudinal floor of 400 - 500 m asl, for the survey. from the information a total area of 5000 m2 was taken into account, consisting of five permanent transects with an area of 1000 m2 each. The study recorded 314 individuals of trees with DAP ≥ 10 cm, represented by 150 species, 91 genera and 36 families, Meliaceae with 14 species, Annonaceae with 11 species, Malvaceae. Moraceae and Sapotaceae with 10 species the most diverse families. The importance value index (IVI) indicated that, the most ecologically important species found in the study area were Iriartea deltoidea Ruiz & Pav with 5.26%, Brosimum utile (Kunth) Oken with 3.47% and Cedrelinga cateniformis Duke with 3.20%, in turn the species that presented a higher IVI did not present a hazard category according to the red book of endemic species of Ecuador; while among the most ecologically important families were Moraceae with 9.28%, followed by Malvaceae with 8.87% and Aracaceae with 7.55%. The Shannon and Simpson diversity indices with values of 4.62 and 0.92 respectively, indicated that the forest studied presents a high diversity of species, while the Sorensen similarity index showed that on average there is a low percentage of similarity between transects. With respect to the diametric structure, the largest number of individuals in the first three diametric classes were recorded, showing in the general distribution of the individuals an inverted J. Keywords: Floristic composition, structure, tropical humid forest, altitudinal floor